The detection of eight putative periodontal pathogens in adult and rapidly progressive periodontitis patients: An institutional study - Joshi Vinayak; Vandana K (Wolters Kluwer Medknow Publications, 2007)
Purpose: Periodontal disease is a commonly prevalent problem faced alike by both the developed and third world countries but showing wide variations in prevalence and severity across different geographical areas. The purpose was to identify Actinobacillus actinomycetemcomitans (Aa), Porphyromonas gingivalis (Pg), Prevotella intermedia (Pi), Ekinella corrodens (Ec), Campylobacter rectus (Cr), Bacteroides forsythus (Bf), Treponema denticola (Td) and Fusobacterium nucleatum (Fn) in Indian adult periodontitis and rapidly progressive periodontitis patients. Materials and Methods: Paper points were used to collect the sample from 28 sites in both adult periodontitis and rapidly progressive periodontitis (8 healthy/20 diseased sites) patients and DNA analysis done. The categorical data was analysed by Fishers exact test and difference in the clinical parameters was tested by Mann-Whitney test. Results: In healthy sites of adult and rapidly progressive periodontitis patients, Aa, Ec, Bf and Aa, Pg, Pi, Td, Fn were detected respectively. However, when diseased and healthy sites were compared in both adult periodontitis and rapidly progressive periodontitis patients respectively, only Pg( P =0.004), Cr( P =0.04), Fn( P =0.014) and Pg( P =0.002), Cr( P =0.02), Fn( P =0.008) were statistically significant. Conclusion: The prevalence of the microorganisms correlate with the clinical parameters like probing depth and bleeding on probing as seen in the Japanese and Western periodontitis patients′ population.